Managing Trust: Translating and the Network Economy - Abdallah, Kristiina; Koskinen, Kaisa (Meta, 2007)
AbstractIn order to understand recent developments in the field of professional translation, we focus in this article on the contemporary network-based translation industry using Albert-Lázsló Barabási’s model of real-world networks and combining it with sociological studies of social capital and trust. According to Barabási, networks are scale-free and therefore fundamentally undemocratic. Barabási’s findings can be used not only by researchers in explaining the topology and organizing principles of production networks but also by professional translators as a conceptual tool in making sense of their current working environment. We use empirical evidence from interviews with six Finnish translators, relating what we discover to be the roles of trust, loyalty, and social capital in networks. The findings suggest that (a lack of) trust may be the Achilles’ heel of these economic networks.